If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + -5) = (x + 1)(x + 7) + 10 Reorder the terms: (5 + x)(x + -5) = (x + 1)(x + 7) + 10 Reorder the terms: (5 + x)(-5 + x) = (x + 1)(x + 7) + 10 Multiply (5 + x) * (-5 + x) (5(-5 + x) + x(-5 + x)) = (x + 1)(x + 7) + 10 ((-5 * 5 + x * 5) + x(-5 + x)) = (x + 1)(x + 7) + 10 ((-25 + 5x) + x(-5 + x)) = (x + 1)(x + 7) + 10 (-25 + 5x + (-5 * x + x * x)) = (x + 1)(x + 7) + 10 (-25 + 5x + (-5x + x2)) = (x + 1)(x + 7) + 10 Combine like terms: 5x + -5x = 0 (-25 + 0 + x2) = (x + 1)(x + 7) + 10 (-25 + x2) = (x + 1)(x + 7) + 10 Reorder the terms: -25 + x2 = (1 + x)(x + 7) + 10 Reorder the terms: -25 + x2 = (1 + x)(7 + x) + 10 Multiply (1 + x) * (7 + x) -25 + x2 = (1(7 + x) + x(7 + x)) + 10 -25 + x2 = ((7 * 1 + x * 1) + x(7 + x)) + 10 -25 + x2 = ((7 + 1x) + x(7 + x)) + 10 -25 + x2 = (7 + 1x + (7 * x + x * x)) + 10 -25 + x2 = (7 + 1x + (7x + x2)) + 10 Combine like terms: 1x + 7x = 8x -25 + x2 = (7 + 8x + x2) + 10 Reorder the terms: -25 + x2 = 7 + 10 + 8x + x2 Combine like terms: 7 + 10 = 17 -25 + x2 = 17 + 8x + x2 Add '-1x2' to each side of the equation. -25 + x2 + -1x2 = 17 + 8x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -25 + 0 = 17 + 8x + x2 + -1x2 -25 = 17 + 8x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -25 = 17 + 8x + 0 -25 = 17 + 8x Solving -25 = 17 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -25 + -8x = 17 + 8x + -8x Combine like terms: 8x + -8x = 0 -25 + -8x = 17 + 0 -25 + -8x = 17 Add '25' to each side of the equation. -25 + 25 + -8x = 17 + 25 Combine like terms: -25 + 25 = 0 0 + -8x = 17 + 25 -8x = 17 + 25 Combine like terms: 17 + 25 = 42 -8x = 42 Divide each side by '-8'. x = -5.25 Simplifying x = -5.25
| 3(x-9)+8=62 | | 2x*7=10 | | (4a+5b)(8a-7b)= | | 260=-v+165 | | 73.543-23.683= | | (2x-1)/4=(x+5)/3 | | 2a+3=(1)/(2)(6+4a) | | 7X=7.5 | | 13x+1=13x+59 | | 5+2(y-7)=3(y+1)-2 | | 2n-7/3 | | 2(2-2)=4 | | 25000-20000-15000=x | | 64-v=231 | | 2x+x+8=6x-3x+8 | | x/6-5 | | 22=-x+215 | | 8P+2=-3P-15 | | 25000-x=20000+15000 | | 7x-5x-7x+1=6x-6x-7 | | 3(x+3)=7x+6-4x+3 | | ma-st=5m+2 | | 10x+30x-8=8(5x+7) | | 1/5x-1/5=-3 | | 7n=8(5n+6) | | 25000-20000=15000+2x | | 10x+30x-8=(5x+7) | | x-4(3x)=0 | | 10/12x=4.5 | | -3/5-6=0 | | 6x+22x-2=7(4x+7) | | 22/12x=-8/12 |